Key Comparison Study - Organic Solvent Calibration Solution - Gravimetric preparation and value assignment of aflatoxin B1 (AfB1) in acetonitrile (ACN) - Josephs, R D; Bedu, M; Daireaux, A; Li, Xiuqin; Li, Xiaomin; Guo, Z; Li, Xianjiang; Choteau, T; Martos, G; Westwood, S; Wielgosz, R I; Li, H; et al. (IOP Publishing, 2022)
Main text The CCQM-K154.b comparison was coordinated by the Bureau International des Poids et Mesures (BIPM) and the Chinese National Institute of Metrology (NIM) on behalf of the Organic Analysis Working Group (OAWG) of the Comité Consultatif pour la Quantité de Matière (CCQM) for National Measurement Institutes (NMIs) and Designated Institutes (DIs) which provide measurement services in organic analysis under the 'Comité International des Poids et Mesures' Mutual Recognition Arrangement (CIPM MRA) and/or have participated in the BIPM's Mycotoxin Metrology Capacity Building and Knowledge Transfer (MMCBKT) project as part of its "Metrology for Safe Food and Feed in Developing Economies" Capacity Building Programme. Gravimetrically-prepared solutions having an assigned mass fraction of specified organic analytes are routinely used to calibrate measurement processes for the quantification of the same analytes in matrix samples. Appropriate assignments of the property value and associated uncertainty of calibration solutions thus underpin the traceability of routine analysis and are critical for accurate measurements. Evidence of successful participation in relevant international comparisons is needed to document calibration and measurement capability claims (CMCs) made by national metrology institutes and designated institutes. In total, eleven NMIs/DIs participated in the Track C, Model II, Key Comparison CCQM-K154.b [Gravimetric preparation and value assignment of aflatoxin B1 (AfB1) in acetonitrile (ACN)] for emerging areas of global interest and innovation. Participants were requested to gravimetrically prepare calibration solutions and value assign the mass fractions, expressed in mg/kg, of aflatoxin B1 (AfB1) in the acetonitrile (ACN) solution. Study samples, with assigned values and associated uncertainties were prepared by the comparison participants and sent to the coordinating laboratory for comparison. The Key Comparison Reference Values (KCRVs), calculated form values measured by the coordinating laboratory based on calibrations obtained from independent gravimetrically prepared calibrant solutions, agreed with participants reported values, within their stated uncertainties. AfB1 was selected to be representative of polar aflatoxins. Aflatoxins are a class of mycotoxins generally produced by fungi of the genus Aspergillus. It was anticipated to provide a challenge representative for the gravimetrical preparation and value assignment of calibration solutions in the mass fraction range of 2 mg/kg to 50 mg/kg of mycotoxins with broadly similar structural characteristics. Nine participants of the MMCBKT programme were provided with a stock solution having a known AfB1 mass fraction and expanded uncertainty to use to gravimetrically prepare and value assign a calibration solution. Three NMIs/DIs also participated using their own calibration solutions. The use of in-house solutions required an additional capacity to undertake a fit-for-purpose purity assessment. NIM was the only NMI participating using both the MMCBKT based and their own in-house assigned solutions in order to connect the two different groups. It was decided to propose separate KCRVs for each of the two ampoules provided by the participating NMIs/DIs based on the AfB1 mass fraction. This allowed participants to demonstrate the efficacy of their implementation of the approaches used to gravimetrically prepare calibration solutions and to assess the AfB1 mass fraction. The majority of the AfB1 mass fraction KCRVs (wKCRV) for CCQM-K154.b spanned a mass fraction range of 2.02 mg/kg to 31.57 mg/kg. The relative expanded uncertainties U(wKCRV) ranged from 0.69 % to 2.93 %. Inspection of the degree of equivalence plots for the AfB1 mass fraction assignments in CCQM-K154.b indicated that there was an excellent agreement of results. Solely, the AfB1 mass fraction assignments of INRAP did not agree with the KCRVs. It was found that the samples were altered as a result of an acid contamination. To reach the main text of this paper, click on Final Report. Note that this text is that which appears in Appendix B of the BIPM key comparison database https://www.bipm.org/kcdb/. The final report has been peer-reviewed and approved for publication by the CCQM, according to the provisions of the CIPM Mutual Recognition Arrangement (CIPM MRA).